One new genus and two new species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Bian, Xun; Xie, Guang-Lin; Chang, Yan-Lin; Shi, Fu-Ming (Zootaxa, 2014)
One new genus, Paraphlugiolopsis Bian & Shi gen. nov., and two new species, Paraphlugiolopsis jiangi Bian & Shi sp. nov. and Paraphlugiolopsis lobocera Bian & Shi sp. nov., are described in the tribe Meconematini. The two new species have similar habitat in Yunnan, China, but live in different altitudes. All material examined is deposited in the Museum of Hebei University.